Cross-sectional analysis of plasma and CSF metabolomic markers in Huntington’s disease for participants of varying functional disability: a pilot study - Andrew McGarry (Nature Portfolio, 2020)
Abstract Huntington’s Disease (HD) is a progressive, fatal neurodegenerative condition. While generally considered for its devastating neurological phenotype, disturbances in other organ systems and metabolic pathways outside the brain have attracted attention for possible relevance to HD pathology, potential as therapeutic targets, or use as biomarkers of progression. In addition, it is not established how metabolic changes in the HD brain correlate to progression across the full spectrum of early to late-stage disease. In this pilot study, we sought to explore the metabolic profile across manifest HD from early to advanced clinical staging through metabolomic analysis by mass spectrometry in plasma and cerebrospinal fluid (CSF). With disease progression, we observed nominally significant increases in plasma arginine, citrulline, and glycine, with decreases in total and d-serine, cholesterol esters, diacylglycerides, triacylglycerides, phosphatidylcholines, phosphatidylethanolamines, and sphingomyelins. In CSF, worsening disease was associated with nominally significant increases in NAD+, arginine, saturated long chain free fatty acids, diacylglycerides, triacylglycerides, and sphingomyelins. Notably, diacylglycerides and triacylglyceride species associated with clinical progression were different between plasma and CSF, suggesting different metabolic preferences for these compartments. Increasing NAD+ levels strongly correlating with disease progression was an unexpected finding. Our data suggest that defects in the urea cycle, glycine, and serine metabolism may be underrecognized in the progression HD pathology, and merit further study for possible therapeutic relevance.